Social Organization as Social Capital in Local Community Empowerment - Hardiati, Enni; Murtiwidayanti, Sri Yuni (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The research is to reveal social activities done by social organization of Nagari Barung-Barung Belantai, Koto XI Tarusan District, Pesisir Selatan Regency, Sumatera Barat Province, to empower local community. The research used qualitative-descriptive apprach, implemented through depth interview, direct observation, documentary analysis, and focus group discussion, with 30 respondents as data resources. The goal of the research is to know the role of social organization as social capital on empowering local community with social welfare through seeing the information, knowledge, attention degree, and community partisipation in social organizations.